I quadri poetici di «Generale» di Francesco De Gregori (Carte Romanze, 2022)
With Generale (opening single from the De Gregori L.P., 1978), Francesco De Gregori paints «a sea of violent, explosive, immediate images of the highest poetic song language». This moving succession of poetic and musical paintings (the hill, the train, Christmas, tears and the return) is one of the most intense of the Italian songwriting tradition. It finds its textual and rhythmic guide in a delicate but firm balance of metric structures, rhetorical figures and lexical choices, internal to the individual stanzas and transversal to the entire composition: their decoding can help to understand the pressing force of this «great song of peace» (Roberto Vecchioni).
Keywords: Francesco de Gregori; Generale; lexicon; metrics; rhetorical figures